Evidence to support IL-13 as a risk locus for psoriatic arthritis but not psoriasis vulgaris. Issue 6 (23rd February 2011) - Bowes, John; Eyre, Steve; Flynn, Edward; Ho, Pauline; Salah, Salma; Warren, Richard B; Marzo-Ortega, Helena; Coates, Laura; McManus, Ross; Ryan, Anthony W; Kane, David; Korendowych, Eleanor; et al.
Abstract : Objective: There is great interest in the identification of genetic factors that differentiate psoriatic arthritis (PsA) from psoriasis vulgaris (PsV), as such discoveries could lead to the identification of distinct underlying aetiological pathways. Recent studies identified single nucleotide polymorphisms (SNPs) in the interleukin 13 ( IL-13 ) gene region as risk factors for PsV. Further investigations in one of these studies found the effect to be primarily restricted to PsA, thus suggesting the discovery of a specific genetic risk factor for PsA. Given this intriguing evidence, association to this gene was investigated in large collections of PsA and PsV patients and healthy controls. Methods: Two SNPs (rs20541 and rs1800925) mapping to the IL-13 gene were genotyped in 1057 PsA and 778 type I PsV patients using the Sequenom genotyping platform. Genotype frequencies were compared to those of 5575 healthy controls. Additional analyses were performed in phenotypic subgroups of PsA (type I or II PsV and in those seronegative for rheumatoid factor). Results: Both SNPs were found to be highly associated with susceptibility to PsA (rs1800925 ptrend = 6.1×10 −5 OR 1.33, rs20541 ptrend = 8.0×10 −4 OR 1.27), but neither SNP was significantly associated with susceptibility to PsV. Conclusions: This study confirms that the effect of IL-13 risk locus is specific for PsA, thus highlighting a key biological pathway that differentiates PsA from PsV. The identification of markers that differentiate the two diseases raises the possibility in future of allowing screening of PsV patients to identify those at risk of developing PsA.